Fenomena Peningkatan Motivasi Bersepeda Masyarakat Di Masa Pandemi Covid-19 - Hijrin Fitroni (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
The existence of the Covid 19 pandemic makes cycling activities in big city people a way of life to maintain fitness. Cycling during the Covid 19 pandemic has increased because cycling is considered to be able to get rid of boredom at home, increase immunity, fill spare time, and increase energy in carrying out daily routines. This study aims to determine the community's motivation for cycling during the Covid 19 pandemic in the city of Surabaya. This research method is survey research. The population in this study were all people who like cycling in the city of Surabaya. The sample in this study were 400 people who have a hobby of cycling who were randomly selected. The instrument used was a questionnaire to measure intrinsic and extrinsic motivation. The results of this study indicate that 50% of the community's motivation for cycling is included in the very high criteria, 48% is included in the high criteria, 2% is included in the moderate category. Intrinsic motivation of the community to cycling by 47% is included in the very high criteria, 50% is included in the high criteria, and 3% is in the moderate category. 67% of the community's extrinsic motivation to cycle is included in the very high criteria, 32% is included in the high criteria, and 1% is in the moderate category.